Integrative Model of Basic Education Curriculum: Integrating Local Wisdom and Global Challenges - Maghfirotul Firmaning Lestari; Fathur Rahman Arrozi; Imron Fauzi; Mukni’ah Mukni’ah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study examines the transformation of the basic education curriculum by integrating local wisdom and global progress. This research stems from the dominance of the current curriculum that emphasizes global aspects and tends to ignore local values . Learning based on local wisdom can strengthen the identity of students and form a character that reflects the culture of the nation. This study uses a qualitative approach and literature, by analyzing documents such as national and international articles and relevant books. The results show that integrating local wisdom and global progress plays an important role in creating a generation that is characterful, competent, and ready to face the challenges of the 21st century. The Integrative Model developed in this study is holistic, contextual, and futuristic and utilizes information and Communication Technology in learning. Educators and policy makers consider this model effective in improving the quality of basic education in Indonesia. This research has implications for the development of a curriculum that is globally relevant and deeply rooted in local cultural values.